Overlap corrections for emissivity calculations of H2O–CO2–CO–N2 mixtures. (January 2018) - Alberti, Michael; Weber, Roman; Mancini, Marco
Highlights: Band overlap corrections concerning gas emissivities of H2 O–CO2 –CO–N2 -mixtures have been calculated using the most recent HITEMP-2010 database. The newly developed overlap correction charts are applicable for temperatures ranging from 500 to 2500 K and pressures ranging from 0.1 to 40 bar pressure. Differences between Hottel's charts and models of Leckner and Modak are highlighted. Abstract: Calculations of total gas emissivities of gas mixtures containing several radiatively active species require corrections for band overlapping. In this paper, we generate such overlap correction charts for H2 O–CO2 –N2, H2 O–CO–N2, and CO2 –CO–N2 mixtures. These charts are applicable in the 0.1–40 bar total pressure range and in the 500 K–2500 K temperature range. For H2 O–CO2 –N2 mixtures, differences between our charts and Hottel's graphs as well as models of Leckner and Modak are highlighted and analyzed.